Representation-independent program analysis. - Strout, Michelle Mills (Software engineering notes.)
Program analysis has many applications in software engineering and high-performance computation, such as program understanding, debugging, testing, reverse engineering, and optimization. A ubiquitous compiler infrastructure does not exist; therefore, program analysis is essentially reimplemented for each compiler infrastructure. The goal of the OpenAnalysis toolkit is to separate analysis from the intermediate representation (IR) in a way that allows the orthogonal development of compiler infrastructures and program analysis. Separation of analysis from specific IRs will allow faster development of compiler infrastructures, the ability to share and compare analysis implementations, and in general quicker breakthroughs and evolution in the area of program analysis. This paper presents how we are separating analysis implementations from IRs with analysis-specific, IR-independent interfaces. Analysis-specific IR interfaces for alias/pointer analysis algorithms and reaching constants illustrate that an IR interface designed for language dependence is capable of providing enough information to support the implementation of a broad range of analysis algorithms and also represent constructs within many imperative programming languages.